Nutritional programming of coenzyme Q: potential for prevention and intervention? - Tarry-Adkins, Jane L. (FASEB J, 2014)
Low birth weight and rapid postnatal growth increases risk of cardiovascular-disease (CVD); however, underlying mechanisms are poorly understood. Previously, we demonstrated that rats exposed to a low-protein diet in utero that underwent postnatal catch-up growth (recuperated) have a programmed deficit in cardiac coenzyme Q (CoQ) that was associated with accelerated cardiac aging. It is unknown whether this deficit occurs in all tissues, including those that are clinically accessible. We investigated whether aortic and white blood cell (WBC) CoQ is programmed by suboptimal early nutrition and whether postweaning dietary supplementation with CoQ could prevent programmed accelerated aging. Recuperated male rats had reduced aortic CoQ [22 d (35±8.4%; P<0.05); 12 m (53±8.8%; P<0.05)], accelerated aortic telomere shortening (P<0.01), increased DNA damage (79±13% increase in nei-endonucleaseVIII-like-1), increased oxidative stress (458±67% increase in NAPDH-oxidase-4; P<0.001), and decreased mitochondrial complex II-III activity (P<0.05). Postweaning dietary supplementation with CoQ prevented these detrimental programming effects. Recuperated WBCs also had reduced CoQ (74±5.8%; P<0.05). Notably, WBC CoQ levels correlated with aortic telomere-length (P<0.0001) suggesting its potential as a diagnostic marker of vascular aging. We conclude that early intervention with CoQ in at-risk individuals may be a cost-effective and safe way of reducing the global burden of CVDs.—Tarry-Adkins, J. L., Fernandez-Twinn, D. S., Chen, J.-H., Hargreaves, I. P., Martin-Gronert, M. S., McConnell, J. M., Ozanne, S. E. Nutritional programming of coenzyme Q: potential for prevention and intervention?